Maternal health care services in primary medical institutions in six regionally representative provinces of China, 2021: a submitted data-based analysis - Xiaojuan ZHANG; Yuan YE; Xiaolin CAO; Yang LIU; Bo PENG; Kun ZHU (Zhongguo gonggong weisheng, 2024)
ObjectiveTo analyze current situation and problems of maternal health care services provided by primary medical institutions in China for making relevant policy recommendations. MethodsDuring May – June 2022, we extracted the data of 2021 on the establishment and operation of obstetrics and gynecology departments submitted by 4 737 township health centers and 1 669 community health service centers in 6 provinces (Zhejiang and Jiangsu, Hubei and Henan, Sichuan and Guizhou representing eastern, central, and western socio-economic regions of China) from the 'Information System of Quality Medical Service at Grassroots Level Program' initiated by National Health Commission. Descriptive statistics and multiple linear regression analysis were conducted using stata16.0 software to examine the status and influencing factors of maternal health care services provided by the primary institutions. ResultsFor the township health centers and community health service centers, the proportions of institutions with gynecology departments were 72.79% (3 448/4 737) and 79.51% (1 327/1 669) and proportions of those with obstetrics departments were 29.07% (1 377/4 737) and 14.92% (249/1 669), respectively; the proportion of the community health service centers with practicing obstetricians and gynecologists was 82.92% (1 384/1 669), higher than that (61.98%, 2 936/4 737) of the township health centers. The provision of obstetrics and gynecology services in the primary medical institutions was relatively low in quality and quantity. For example, the proportions of township health centers and community health service centers providing midwifery for women with singleton delivery were 22.38% (1 060/4 737) and 10.37% (173/1 669), respectively, with an average daily service of less than one midwifery process. The equipment allocation rates for automatic biochemical analyzers and other related instruments were above 80% for all the primary institutions. The proportions of township health centers and community health service centers supplied with at least one type of drugs on uterine contraction were 51.11% (2 421/4 737) and 49.13% (820/1 669) respectively. The results of multivariate linear logistic regression analysis showed that region, number of staff in active service, number of beds available, proportion of pregnant women with contracted service, and equipment of color Doppler ultrasound instrument had significant influence on the rates of pregnant women registration in first trimester and postpartum visit; the establishment of gynecology departments only had a significant impact on the rate of postpartum visitation. ConclusionThe capability of maternal health services in primary medical institutions is gradually shrinking, and some of the institutions cannot meet the conditions for providing maternal health care services and can only assume responsibility for information management. The assessment criteria and service content of maternal health projects in primary medical institutions need to be adjusted urgently.